Severe malaria during pregnancy at the maternity ward of the municipal medical center of Ratoma, Guinea-Conakry - Diallo, Mamadou H.; Baldé, Ibrahima S.; Barry, Alpha B.; Sylla, Ibrahima; Diallo, Fatoumata B.; Sagno, Christine; Keita, Namory (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Gestational malaria remains a major public health problem in malarious areas. The objectives of this work were to describe the socio-demographic, clinical, paraclinical, therapeutic and prognostic characteristics of patients who developed severe malaria during pregnancy. Methods: It was a descriptive prospective study carried out in the maternity ward of Ratoma municipal medical center, which was carried out over a period of 6 months from 01 October 2018 to 31 March 2019. This study involved all pregnant women who had presented severe malaria according to WHO criteria. Results: The incidence of severe malaria during pregnancy was 7%. The average age of our patients was 22.4 years with extremes of 15 and 47 years. The symptomatology that motivated the consultation was variable, the most frequent signs were: hyperthermia (100%), headache (79%), vomiting (99%). The general examination at admission objectified a fever with an average temperature of 39°C with extremes of 38-40.4°C. All patients had a positive rapid diagnostic test (RDT) as well as their thicker drop. The hemogram revealed the existence of a more or less severe anemia in 89.9% of cases. All patients were treated with parenteral quinine (100%). Maternal lethality was 1.8%. After severe malaria, 70 patients (62.5%) carried their pregnancy to term and 40 delivered an eutrophic child (35.71%), 30 (26.78%) delivered a hypotrophic child, 20 (17.85%) had a spontaneous abortion, premature delivery was observed in 10 patients (8.9%), and fetal death in utero was observed in 12 patients (10.71%). Conclusions: All patients had received parenteral quinine curative therapy. Maternal and perinatal complications were common. To improve this prognosis, intermittent preventive treatment and the use of insecticide-treated nets, which are the most effective prevention method at this time, must be further promoted in anticipation of the much hoped-for vaccine.